PUBLIC FINANCING OF SPORT IN SANTA CATARINA: THE FUNDESPORTE AND ALLOCATION OF FUNDS. (Fiep Bulletin - online, 2014)
Practicing sports is no formal duty of the State, the same being a social right of all citizens. In the state of Santa Catarina sport management is linked to the State Department of Tourism, Culture and Sport (SOL), which through the Sports Incentive Fund (FUNDESPORTE) funding sports projects The aim of this study was to analyze the distribution of resources for the projects submitted to FUNDESPORTE in 2012. Were analyzed projects statewide, nationally and internationally. V The total amount paid in 2012 was R $ 8,095,007.00. Regarding the sports in 2012 were awarded 32 modalities. From the analysis, we conclude that the year 2012 the FUNDESPORTE allocated a large portion of its resources to large events hosted in the State, which hurts other sports events which by law should be prioritized, as is the case sport education.
Keywords: Public Policies; FUNDESPORTE; Financing of Sport